Barcodes for mobile devices - Kato, Hiroko 1963- (Cambridge University Press, 2010)
"From inventory management in stores to automotive part tracking in assembly plants, barcodes are one of the most prevalent automatic identification and data capture technologies. This book provides a complete introduction to barcodes for mobile devices, presenting the most relevant and up-to-date information previously unavailable elsewhere or difficult to obtain. The focus throughout is on recent developments and two-dimensional (2D) barcodes, including the research and development steps towards colour barcodes for mobile devices, helping readers to develop their own barcodes. The authors also provide design details for their own novel colour 2D barcode: the Mobile MultiColour Composite (MMCC) barcode, plus coverage of RFID technology and one-dimensional barcodes. This book is ideal for professional developers of barcodes for mobile devices who need the latest technical details and information on how to develop barcodes. It is also a useful reference for graduate students researching the field of barcode technology and mobile computing"--Provided by publisher.